The Mediating Effect of Emotional Intelligence on Sustainability and Future Business Performance - Susan Tee Suan Chin; Rosman Md Yusoff (Center for Risk Management & Sustainability and RSF Press, 2021)
The COVID-19 pandemic has engulfed numerous parts of the world, crippling economies. Many countries’ government has issued lockdown orders to curb the spread of the COVID-19 virus. This lockdown has created a new norm for society. Unfortunately, businesses have been badly affected by the lockdown. Thus, business leaders needed to dig deep and think of ways to sustain their organisation and move forward. This study selected a successful manufacturing company and examined the mediating effects of emotional intelligence against two other variables, namely organisational citizenship behaviour and job satisfaction of the company’s executives during the challenging situation. The questionnaires were adapted from Palmer and Stough (to determine emotional intelligence) and Podsakoff et al. (to examine organisational citizenship behaviour) and were emailed to the executives via the human resource manager. The survey was participated by 110 executives. Results revealed that emotional intelligence played a mediating role in enhancing organisational performance.